Genomic Characterization of ESBL- and Carbapenemase-Positive Enterobacteriaceae Co-harboring mcr-9 in Japan - Nakamura, Akihiro; Nakamura, Tatsuya; Niki, Makoto; Kuchibiro, Tomokazu; Nishi, Isao; Komatsu, Masaru (Frontiers in Microbiology, 2021)
Worldwide spread of Enterobacteriaceae resistant to colistin, a polypeptide antibacterial drug for last-resort treatment of carbapenemase-producing Enterobacteriaceae (CPE) infections, is concerning. This study aimed to elucidate colistin MICs and molecular characteristics of mcr-1 to mcr-9 of ESBL-producing Escherichia coli (ESBL-Ec) and CPE in Japan and clarify the genomic structure of strains harboring the mcr gene (especially mcr-9). This study included 168 ESBL-Ec and 126 CPE strains isolated at Japanese medical facilities. Colistin susceptibility testing and multiplex PCR targeting mcr-1 to mcr-9 were performed for all strains with S1-nuclease pulsed-field gel electrophoresis, Southern blot hybridization, and whole-genome sequencing with hybrid assembly performed for mcr gene-carrying strains. Two CPE strains showed a MIC ≥4 µg/mL in colistin susceptibility testing, with no known resistance mechanism detected. However, PCR conducted on all target strains detected three mcr-9-carrying strains showing colistin susceptibility. The blaCTX-M-62-positive E. coli THUN648 strain simultaneously carried blaCTX-M-62 and mcr-9 on a 275-kbp plasmid. Besides, blaIMP-6 + blaCTX-M-2-positive Klebsiella pneumoniae THUN262 and blaGES-24-positive Enterobacter kobei THUN627 had mcr-9 encoded on the chromosome. Only THUN627 encoded qseB/C, which is suggested to be a regulatory gene for mcr-9, downstream of mcr-9. However, this strain showed no increased expression of these genes in mRNA quantitative analysis under colistin exposure. Colistin MICs of ESBL-Ec and CPE in Japan were all below 2 µg/mL, indicating susceptibility. Several colistin-susceptible Enterobacteriaceae carrying silent mcr-9 encoded on plasmids and chromosomes have already spread worldwide along with other antimicrobial resistance genes. However, the mechanism of colistin resistance by mcr-9 remains unclear.